Implementasi Rezim Commission for The Conservation Of Southern Bluefin Tuna (CCSBT) di Indonesia: Ketidakpatuhan Total Allowable Catch Southern Bluefin Tuna - Widiarso, Antonius; Utomo, Tri Cahyo; Pattipelohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Indonesia, as a member of CCSBT since 2008, is obliged to comply with the amount ofTAC granted annually to safeguard southern bluefin tuna population. Indonesia is one ofthe important members of CCSBT because Indonesia is the only breeding ground forsouthern bluefin tuna, precisely at Java Sea. In an effort to implement TAC, Indonesia isnoted to have difficulties to comply with the number determined by CCSBT. From 2008 to2014, Indonesia only adhered to TAC in 2009 and 2010. The author uses regimecompliance concepts in analyzing factors affecting Indonesia's non-compliance with TACimplemented by CCSBT. The research method used by the author in this study isqualitative method. In addition, this study is an explanatory study. After analyzing the data,it was concluded that Indonesia's non-compliance with TAC implemented by CCSBT canbe explained by factors such as ambiguity, capacity limitations and temporal dimension.